Potentialities of Post-Media: Networks of Resistance and Subjugation in Félix Guattari's A Love of UIQ. - Bandosz, Benjamin (Deleuze & Guattari Studies, 2021)
Félix Guattari's theoretical and practical interests in cinema culminated in the film project A Love of UIQ. While critics have concentrated on the sci-fi screenplay's elements of minor cinema, its themes of mass media, emerging computer technologies and informatic-communication networks particularly express Guattari's concept of post-media. The screenplay is an aesthetic meditation on the potentialities of post-media, a concept that anticipates the practical and theoretical issues surrounding the age of the Internet. A Love of UIQ voices Guattari's ambivalence towards the liberatory possibilities of network technologies that are at constant risk of capitalist recapture.